Early multidisciplinary prevention program of post-stroke shoulder pain: A randomized clinical trial. (August 2022) - Glize, Bertrand; Cook, Amandine; Benard, Antoine; Sagnier, Sharmila; Olindo, Stéphane; Poli, Mathilde; Debruxelles, Sabrina; Renou, Pauline; Rouanet, François; Bader, Clément; Dehail, Patrick; Sibon, Igor
Objective: To evaluate if positioning the upper-limb promoting abduction, external rotation and flexion of the shoulder reduces the intensity of post-stroke shoulder pain at day-7 compared to usual clinical practice. Design & setting: Prospective single-center randomized clinical trial using a superiority design comparing two preventive strategies of post-stroke shoulder pain in a stroke unit. Subjects: Patients were included within 2 days from a first symptomatic ischemic stroke affecting shoulder motor function. Interventions: Intervention group included specific positioning of the shoulder in abduction, external rotation and flexion in bed, chair and during mobilization. Control group referred to usual practice i.e. positioning using a standard support scarf. Main measures: Primary outcome was the intensity of shoulder pain assessed by the visual analog scale (VAS) (0–100) at day-7 post-stroke. Other outcomes measured at day-7 and 2 months post-stroke were the VAS, motor function, spasticity, depression, functional independence and rates of complex regional Pain syndrome (CRPS). Results: 76 patients (49 males; mean age = 68.3) were randomized. The shoulder pain at day-7 was not different between the control group (16.1, SD = 27.4) and the intervention group (10.3, SD = 21.5, p = 0.18) as well as at 2 months ( p = 0.12). A lower rate of depression was observed in the intervention group at 2 months 36.7% (CI95% 19.9;56.1) vs 52.9% (CI95% 35.1;70.2). No between-group difference in other outcomes was observed at 2 months. Conclusions: This study failed to demonstrate the benefit of a specific positioning tool in reducing the intensity of post-stroke shoulder pain which was lower than previously reported in the literature.